2018
DOI: 10.1021/acs.jafc.8b00540
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fungicides and Microalgal Phenolic Extracts for the Direct Control of Fumonisin Contamination in Maize

Abstract: Fungicides and, for the first time, microalgal phenolic extracts (MPE) from Spirulina sp. and Nannochloropsis sp. were applied on maize culture media under field conditions to evaluate their ability to minimize Fusarium species development and fumonisin production. An in vitro assay against F. verticillioides was carried out using maize grains as the culture medium. An open-field experiment was carried out in Northwest Italy under natural infection conditions. The compared treatments were factorial combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…For example, microalgae or cereals extract was found to be rich in phenolic acids (e.g., gallic, caffeic, and chlorogenic acids). Results showed that these natural acids have an inhibitory activity against the production of many mycotoxins such as fumonisin B1 (FB1), OTA, and type B trichothecenes (TCTB) (Christ‐Ribeiro et al., 2019; Pagnussatt et al., 2014; Scaglioni et al., 2018; Scaglioni, Pagnussatt, et al., 2019). Moreover, the reuse of agro‐industrial by‐products is a valuable source of phenolic compounds.…”
Section: Strategies To Fight Against Toxigenic Fungi and Mycotoxin Pr...mentioning
confidence: 99%
“…For example, microalgae or cereals extract was found to be rich in phenolic acids (e.g., gallic, caffeic, and chlorogenic acids). Results showed that these natural acids have an inhibitory activity against the production of many mycotoxins such as fumonisin B1 (FB1), OTA, and type B trichothecenes (TCTB) (Christ‐Ribeiro et al., 2019; Pagnussatt et al., 2014; Scaglioni et al., 2018; Scaglioni, Pagnussatt, et al., 2019). Moreover, the reuse of agro‐industrial by‐products is a valuable source of phenolic compounds.…”
Section: Strategies To Fight Against Toxigenic Fungi and Mycotoxin Pr...mentioning
confidence: 99%
“…The results obtained under naturally infected field conditions and over three growing seasons confirmed that the control of the second generation larvae of ECB, by means of an insecticide application, was able to consistently reduce the severity of fungal ear rot and the contamination of FBs in grains intended for human consumption grown in non-Bt maize growing areas [ 6 , 22 ], and also resulted in a significant increase in grain yield. The effect of insecticides in minimizing the FB content was also consistent for the considered production situation of maize cultivated specifically for the food supply chain, in which all the preventive agronomic practices that are able to minimize the injuries of ECB and mycotoxin occurrence, such as early sowing and early harvest times and the careful management of plant density, fertilization and irrigation to avoid any plant stress, had already been applied [ 14 ].…”
Section: Discussionmentioning
confidence: 66%
“…Masiello et al [ 20 ] demonstrated that DMI fungicides, and prothioconazole in particular, are the most effective molecules against several strains of F. graminearum , F. verticillioides , F. proliferatum and A. flavus . Scaglioni et al [ 22 ] and Li et al [ 29 ] highlighted that tebuconazole and its enantiomers clearly inhibit F. verticillioides growth and could also reduce FB production, although the latter study reported that the effect could differ according to the environmental factors, such as the temperature and the water activity. Furthermore, some in vitro studies have highlighted that the use of fungicides could stimulate mycotoxin production in both the Fusarium Liseola section [ 30 ] and the Discolor section [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental factors, including the biotic and abiotic factors, significantly affect fungal growth and mycotoxin production. Among these factors, a w and temperature have important effects, and the antifungal substances are also an important factor. Thus, abiotic factors can activate or inhibit the biosynthesis of FBs. The studies already clarified that at least 17 genes, which were clustered together, are responsible for the FB biosynthesis.…”
Section: Introductionmentioning
confidence: 99%